Kaji-Ichigoside F1 and Rosamultin Protect Vascular Endothelial Cells against Hypoxia-Induced Apoptosis via the PI3K/AKT or ERK1/2 Signaling Pathway. (30th March 2020) - Shi, Chaofeng; Zhan, Li; Wu, Yuqiang; Li, Zhengchao; Li, Jianyu; Li, Yaxiao; Wei, Jinxia; Zhang, Yongliang; Li, Lingzhi
Abstract : As a pair of differential isomers, Kaji-ichigoside F1 and Rosamultin are both pentacyclic triterpenoids isolated from the subterranean root of Potentilla anserina L., a plant used in folk medicine in western China as antihypoxia and anti-inflammatory treatments. We demonstrated that Kaji-ichigoside F1 and Rosamultin effectively prevented hypoxia-induced apoptosis in vascular endothelial cells. We established a hypoxia model, using EA.hy926 cells, to further explore the mechanisms. Hypoxia promoted the phosphorylation of AKT, ERK1/2, and NF- κ B. In hypoxic cells treated with Kaji-ichigoside F1, p-ERK1/2 and p-NF- κ B levels were increased, while the level of p-AKT was decreased. Treatment with Rosamultin promoted phosphorylation of ERK1/2, NF- κ B, and AKT in hypoxic cells. Following the addition of LY294002, the levels of p-AKT, p-ERK1/2, and p-NF- κ B decreased significantly. Addition of PD98059 resulted in reduced levels of p-ERK1/2 and p-NF- κ B, while p-AKT levels were increased. Pharmacodynamic analysis demonstrated that both LY294002 and PD98059 significantly inhibited the positive effects of Kaji-ichigoside F1 on cell viability during hypoxia, consistent with the results of hematoxylin-eosin (H&E) staining, DAPI staining, and flow cytometry. The antihypoxia effects of Rosamultin were remarkably inhibited by LY294002 but promoted by PD98059. In Kaji-ichigoside F1- and Rosamultin-treated cells, Bcl2 expression was significantly upregulated, while expression of Bax and cytochrome C and levels of cleaved caspase-9 and cleaved caspase-3 were reduced. Corresponding to pharmacodynamic analysis, LY294002 inhibited the regulatory effects of Kaji-ichigoside F1 and Rosamultin on the above molecules, while PD98059 inhibited the regulatory effects of Kaji-ichigoside F1 but enhanced the regulatory effects of Rosamultin. In conclusion, Kaji-ichigoside F1 protected vascular endothelial cells against hypoxia-induced apoptosis by activating the ERK1/2 signaling pathway, which positively regulated the NF- κ B signaling pathway and negatively regulated the PI3K/AKT signaling pathway. Rosamultin protected vascular endothelial cells against hypoxia-induced apoptosis by activating the PI3K/AKT signaling pathway and positively regulating ERK1/2 and NF- κ B signaling pathways.